2019
DOI: 10.1002/cphc.201900824
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Orientational Disorder on the Optical Absorption Properties of the Hybrid Metal‐Halide Perovskite CH3NH3PbI3

Abstract: An experimental and theoretical investigation is reported to analyze the relation between the structural and absorption properties of CH3NH3PbI3 in the tetragonal phase. More than 3000 geometry optimizations were performed to reveal the structural disorder and identify structures with the lowest energies. The electronic structure calculations provide an averaged band gap of 1.674 eV, which is in excellent agreement with the experimental value of about 1.6 eV. The simulations of the absorption spectrum for thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…Such an accuracy is expected at this level of theory for MAPb(I 1−x Br x ) 3 and stays in agreement with our previous results on MAPbI 3 . 11 Both experimental and theoretical results show that the band gap increases linearly for bromine doping ranging from 0 to 10%. It can be mentioned that previous experimental results 12 have demonstrated that the band gap displays a quadratic behavior as a function of bromine composition in the entire 0−100% doping range.…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…Such an accuracy is expected at this level of theory for MAPb(I 1−x Br x ) 3 and stays in agreement with our previous results on MAPbI 3 . 11 Both experimental and theoretical results show that the band gap increases linearly for bromine doping ranging from 0 to 10%. It can be mentioned that previous experimental results 12 have demonstrated that the band gap displays a quadratic behavior as a function of bromine composition in the entire 0−100% doping range.…”
Section: Resultsmentioning
confidence: 83%
“…Figure 2 shows the UV−vis absorption spectrum for different bromine atom concentrations. In our last work, Martynow et al 11 assigned the maximum absorption peaks for MAPbI 3 without bromine atoms. It is observed that the overall shape of the spectrum is not changed for different doping compositions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations